Efficacy of Yellow oleander (Thevetia neriifolia Juss) seed extract on the growth and development of Tribolium castaneum (Herbst) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Thevetia neriifolia; seed extract; Tribolium castaneum; growth and development Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 49-52